1992
DOI: 10.1007/bf03160543
|View full text |Cite
|
Sign up to set email alerts
|

Nektonic invertebrate abundance and distribution at the emergent vegetation-open water interface in the Delta Marsh, Manitoba, Canada

Abstract: Water temperatures were constant across the interface through much of the year. By mid-summer, hypoxic conditions prevailed within the water column in the cattail stand. Algae levels were similar across the interface throughout much of the year, with peaks occurring just inside the interface in June and July. Early in the season, there was a trend for higher nektonic invertebrate numbers within the cattail stands of both bays. By late August, there were similar total invertebrate numbers across the interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…Studying the succession of a phytoplankton community has important theoretical and practical significance. Numerous research studies in different rivers have showed that temperature, light and nutrients are important factors impacting the succession of the phytoplankton community [2][3][4]. In natural water bodies, these factors often simultaneously determine the succession of the phytoplankton community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the succession of a phytoplankton community has important theoretical and practical significance. Numerous research studies in different rivers have showed that temperature, light and nutrients are important factors impacting the succession of the phytoplankton community [2][3][4]. In natural water bodies, these factors often simultaneously determine the succession of the phytoplankton community.…”
Section: Introductionmentioning
confidence: 99%
“…The aims of our research were (1) to verify differences in the trophic states and phytoplankton community structures in three tributaries of the Dongjiang River; (2) to examine how the phytoplankton community variation is influenced by environmental factors; and (3) to summarize the seasonal variation in the phytoplankton communities of the three rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Seybold et al, 2002 andMurkin et al, 1992) and shallow lakes (e.g. Ansa-Asare et al, 1999), few studies have been conducted on the increasing number of re-created wetland environments where rapid development of habitat and active management are key characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of emergent vegetation has been well documented for waterbirds that use wetlands during migration and breeding . Emergent vegetation provides shelter and a substrate for invertebrates (Murkin et al 1992), and there is evidence that invertebrate abundance is greater when open water is interspersed with emergent vegetation (Voigts 1976). Indeed, waterbird abundance and species richness tend to be greatest when emergent vegetation and open water is present at a 1:1 ratio , Kaminski and Prince 1984.…”
Section: Discussionmentioning
confidence: 99%
“…With prolonged flooding, the invertebrate community changes, submergent vegetation proliferates, and the emergent vegetation may eventually begin to die back and become more patchily distributed due to inundation and muskrat activity Davis 1978, Murkin and. Overall, this results in habitat that is favored by nesting by marsh birds, particularly during this degenerating phase when openings in the robust vegetation become numerous (Murkin et al 1992, Murkin and Ross 1999. Yellow-headed Blackbirds and Marsh Wrens, obligate wetland breeders, build nests using robust vegetation , Twedt and Crawford 1995.…”
Section: Discussionmentioning
confidence: 99%